Boron Compounds as Additives for the Cationic Polymerization Using Coumarin Derivatives in Epoxy Silicones. Issue 2 (16th December 2020) - Abdallah, Mira; Hijazi, Akram; Cozzi, Pier Giorgio; Gualandi, Andrea; Dumur, Frederic; Lalevée, Jacques
Abstract: This work aims at using two borane derivatives, namely Borane A: B(C6 F5 )3 and Borate B: C32 H12 BF24 Na as additives for the cationic polymerization of epoxy silicones under visible light, in the presence of coumarins as photosensitizers and 4‐isopropyl‐4′‐methyldiphenyl iodonium tetrakis(pentafluorophenyl)borate (SC939). The effect of boron compounds on the absorption and the emission spectra of a coumarin is particularly outlined. These two boron compounds can improve both the polymerization rate and the final monomer conversion. Moreover, the effect of adding water on the reactivity of the system is studied. It should be noted that the studied boron additives are able to enhance in an interesting way the polymerization rate when light irradiation is switched off through a dark polymerization (DP) mechanism. This latter behavior is highly desired for practical applications. Finally, the very high photoreactivity of boron compounds is employed for the development of new cationic 3D printing resins upon exposure to a light emitting diode (LED) projector at 405 nm, as well as for direct laser write experiments, by means of a laser diode at 405 nm. The 3D polymerization occurs through a cationic process which can be quite useful in order to reduce the shrinkage usually observed in radical polymerization. Abstract : This work aims at using two borane derivatives, namely Borane A: B(C6 F5 )3 and Borate B: C32 H12 BF24 Na as additives for the cationic polymerization of epoxy‐silicones under visible light. The very high photoreactivity of boron compounds is employed for the development of new cationic 3D printing resins upon exposure to an LED projector at 405 nm.